Analysis Place Branding as a Local Culture Kampung Naga West Java Indonesia (International Journal of Management and Sustainability, 2016)
The purpose of this study is to describe the situation and condition of place branding local culture ethnic villages, determining factors of place branding that will be the basis for further strengthen an area icon, it will generate factors of place branding so that the area can determine which factors will be retained as a characteristic of the region, making attractive icons to be used as place branding is a ethnicvillage, which has been the ethnic village does not have a powerful icon to be used as selling points both for the local market and market global. For the respondents are either tourists, guide, organization commitee, and chairman of the organization. To view these researchers will use AHP (Analytical Hierarchy Process).